دور الجامعة في تحقيق الذكاء الاستراتيجي وتنمية رأس المال الفكري من وجهة نظر أعضاء هيئة التدريس: جامعة المنصورة نموذجا - منصور، منار منصور أحمد (جامعة سوهاج - كلية التربية, 2021)
هدف البحث إلى تحديد دور الجامعة في تحقيق الذكاء الإستراتيجي وتنمية رأس المال الفكري من وجهة نظر أعضاء هيئة التدريس بجامعة المنصورة، وما إذا كان هناك فروق في تقدير دور الجامعة في تحقيق الذكاء الإستراتيجي وتنمية رأس المال الفكري من وجهة نظر أعضاء هيئة التدريس وفقا لمتغير الجنس، وتم استخدام المنهج الوصفي، وطبقت استبانة لتحقيق هدف الدراسة، وتوصلت الدراسة إلى أن للجامعة دور في تحقيق الذكاء الإستراتيجي بأبعاده المختلفة (الاستشراف، تفكير النظم، الشراكة، التحفيز) تراوح بين درجة كبيرة ومتوسطة لمعظم العبارات بالأبعاد، ووجد عدد من المعوقات التي تحول دون تحقيق الذكاء الاستراتيجي كان من أبرزها ضعف المخصصات المالية، وكثرة أعباء ومهام أعضاء هيئة التدريس، كما وجدت العديد من المتطلبات التي ينبغي توافرها لتحقيق الذكاء الاستراتيجي ومنها تنمية مهارات أعضاء هيئة التدريس، وتطوير البرامج الدراسية، وتطوير مهارات القيادات، وتتوافر بعض مظاهر تنمية رأس المال الفكري بالجامعة مثل امتلاك الجامعة لقيادة ذات رؤية واضحة محددة، وامتلاك الأعضاء خبرة طويلة في مجال عملهم، وجاءت الفروق بين أعضاء هيئة التدريس وفقا للجنس في تقدير دور الجامعة في تحقيق الذكاء الاستراتيجي وتنمية رأس المال الفكري دالة لأبعاد الذكاء الاستراتيجي ورأس المال الفكري، وأوصت الدراسة بضرورة إنشاء وحدة للذكاء الاستراتيجي، وتزويد القادة بالجامعة بالمعارف الحيوية والضرورية، والاهتمام بتنمية رأس المال الفكري حيث أنه الركيزة الأساسية للتطوير المستقبلي بالجامعات، وأن يكون معيار الذكاء الاستراتيجي من معايير اختيار القيادات الجامعية.
The aim of this research is to determine the university’s role in achieving strategic intelligence and developing intellectual capital from the viewpoint of the faculty members at Mansoura University and whether there are differences in assessing the university’s role in achieving strategic intelligence and developing intellectual capital from the point of view of faculty members according to the gender variable. The descriptive approach was used, and a questionnaire was applied to achieve the goal of the study. The study concluded that the university has a role in achieving strategic intelligence in its various dimensions (orientalism, systems thinking, partnership, motivation), ranging from a large to medium degree to most expressions in dimensions and a few obstacles that prevent the achievement of strategic intelligence were found, the most prominent of these obstacles are the lack of financial allocations, and the large burdens and tasks of faculty members. Many requirements are found that should be met to achieve strategic intelligence, including developing the skills of faculty members, developing study programs, and developing leadership skills. There are some aspects of the university’s intellectual capital development, such as the university’s possession of leadership with a clear vision, and the members ’possession of long experience in their field of work. The differences between faculty members according to gender in assessing the university’s role in achieving strategic intelligence and developing intellectual capital are significant in all dimensions of strategic intelligence and intellectual capital. The study recommended the necessity of establishing a unit for strategic intelligence and providing university leaders with vital and necessary knowledge and attention to the development of intellectual capital as it is the main pillar for future development of universities, and that the criteria of strategic intelligence should be one of the most important rules for selecting university leaders.
Keywords: الجامعات -- أعضاء هيئة التدريس -- الذکاء الإستراتيجي -- رأس المال الفكري -- جامعة المنصورة